Animation a handy guide - Graber, Sheila (A. & C. Black, 2009)
This handy guide is just that. It is small enough to handle and carry around easily, and is a must-have resource for everyone interested in animation history,theory and practice. Each of the 10 sections is linked to a practical "Stuff for Students" section which gives clever first-hand instructions for animating anything from plasticine to pixels.